Behavioral Psychedelics: Integrating Mind and Behavior to Improve Health and Resilience - Neuhaus, Edmund C.; Slavich, George M. (Frontiers in Psychiatry, 2022)
One of the most recent and potentially exciting advancements in the health sciences has involved the attempted use of psychedelics for treating mental and behavioral health problems, such as depression, posttraumatic stress disorder, and addiction. Despite surging scientific and public interest in this work, however, we presently have no standard of care or consensus regarding how best to combine psychotherapy and psychedelics or assess effectiveness. We discuss these timely issues here through the lens of behavioral psychedelics, which we define as the study of psychedelics to foster intentional changes in habits and behaviors to improve health and resilience. Psychedelics has the potential to reduce chronic disease risk caused by mental and behavioral rigidity. To fully realize this potential, though, we believe the field must establish best practices and guidelines that include how to effect lasting changes in behavior.